Rural small-scale industries: profile, constraints and policy issues - Chamhuri Siwar; Abdul Hamid Jaafar; Ahmad Md Zin. (Universiti Kebangsaan Malaysia, 1994)
Please refer fulltext/Sila rujuk teks penuh